Nefropatía asociada a la enfermedad de Cushing en el canino : estudio de variables de valor predictivo de daño renal - Vidal, Patricia Noemí (2019)
Cushing's disease (CD) is characterized by chronic hypercortisolism, which cause metabolic and systemic alterations. It is associated to a lot of comorbidities,\nhypertension is one of them, which leads along with hypercortisolism, to kidney\ndisease, and both have an impact on coagulation parameters which develops in an hypercoagulability state with thrombosis risk.\nTaken all this to account, CD?s dogs were studied. The results showed an important\ndecrease in nitric oxide (NO) correlated with the increase in cortisol (r = -0.67, P\n<0.0001), and both were associated with an increase in blood pressure [(PS and\ncortisol (r = 0.46, P = 0.008) PS and NO (r = - 0.87; P <0.0001)], specially with\ndiastolic pressure (PD). PD correlated with cortisol (r = 0.63, P <0.0001) positively and with NO (r = -0.81; P <0.0001). All this has an impact in renal parameters affecting the glomerular filtration rate (GFR) (r = - 0.58, P = 0.007) and increasing proteinuria,\nevidenced by the increase in protein/creatinine ratio in urine (UPC) (r = 0.8, P <0.001), which is an indicator of early glomerular damage. Using Resistance Index (IR) related\nto the UPC and blood pressure have a high prognostic value of renal affection. To decided what treatment is the most effective renoprotective and hypotensive therapy, a\ncomparison was made between 2 groups of CD?s dogs according to the UPC value, they were also subdivided according to arterial pressure. enalapril vs doxazosina were\ncompared. The comparison was made between all the gropus. Dozaxosine was the\nmost effective in reducing UPC (*P-valueBvsE= 0,01) and blood pressure (PS: PvalueBvsE = 0,01 and P-valueBvsD= 0,029; PD P-valueBvsE = 0,002).\nThe hypercoagulability state in CD?s dogs was confirmed, a comparison between a\ncontrol group (healthy dogs) and cushing?s dogs was made, it was found in cushing?s dogs a high concentrations of von-Willebrand Factor (FvW) and plasminogen activator\ninhibitor-1 (PAI-1) (P-value = 0.003 and P-value = 0.002 respectively), and a decreased in activity of Antithrombin III (ATIII), which was associated with an increase of UPC (r =\n-0.75, P-value <0.001 ) and presence of D-Dimer + (DD) (r = -0.5, P-value = 0.008),\nhaving a correlation in both cases. Those results have a great utility as early indicators of thrombosis risk or pulmonary thromboembolism (TEP). Indicators associated with\nclinical symptoms and a possitive lung thrombosis image are needed to confirm the TEP. To explain one of the mechanisms involved in the development of hypertension, the\nconcentrations of aldosterone and angiotensin II (Ang II) in CD?s dogs were compared\nwith a group of healthy dogs. The results showed that aldosterone would not be\ninvolved, becuase the concentration was the same in healthy controls as CD?s dogs (P-valor= 0,8), but Ang II was found increased in cushing?s dogs (P-valor< 0,0001), which means that it has a rol in cushing's hypertension. The resaults of this research thesis has a great relevance to expand the knowledge in\nthe pathophysiology of this disease. It will help to improve the early diagnosis of these comorbidities and to implement appropriate preventive therapies in the daily clinic which will improve the quality life and survival of the patient.